All the seas of the world - Kay, Guy Gavriel (Berkley, 2022)
"On a dark night along a lonely stretch of coast, a small ship sends two people ashore. Their purpose is assassination. They have been hired by two of the most dangerous men alive to alter the balance of power in the world. If they succeed, the consequences will affect the destinies of empires, and lives both great and small. One of those arriving at that beach is a woman abducted by corsairs as a child and sold into years of servitude. Having escaped, she is trying to chart her own course-and is bent upon revenge. Another is a seafaring merchant who still remembers being exiled as a child with his family from their home, for their faith, a moment that never leaves him. In what follows, through a story both intimate and epic, unforgettable characters are immersed in the fierce and deadly struggles that define their time. All the Seas of the World is a drama that also offers moving reflections on memory, fate, and the random events that can shape our lives-in the past, and today"--